On kinetic features of photo- or g-induced polymerization in p-diethynylbenzene crystals in the temperature range of 4.2-300 K - Gordon, D.A.; Mikhaylov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The stereoregular radical polymerization in photo- or g-irradiated crystals of p-diethynylbenzene (DEB) has been found to proceed in the temperature range of 4.2–300 K [J. Low Temp. Phys. 139, 675 (2005)]. We have studied the kinetics of this process. The polymerization of acetylene monomers due to the system of conjugated bonds formation results in the shift of a crystal absorption band from UV to visible. Being compared with gravimetrical data on the polymer yield, it allowed the direct detection of polymerization process in a crystal. The monomer radicals, initiating the polymerization process, as well as propagating macroradicals were detected by ESR method. The rates of both radical formation and chemical reaction of polymerization retard, as it inherent to solid phase processes, already at small yields. Thus we applied a mechanism pertaining to the first stages of the processes only. It has been proved that both photo- and g-induced polymerization have chain character in the temperature range 77–300 K but it is most probably not chained at 4.2 K and, for photo-polymerization, every act of monomer addition to the polymer needs an extra quantum of light. The kinetic chain length (the number of added monomer molecules per radical) turned out to be around of 200 at 300 K and of 20 at 77 K. It was interesting to note that polymer just formed was able to be modified — the radicals then created in polymer chain were able to add monomer molecules forming, in such a way, a branched polymer. This process, of course, is not chained too.